Penerapan Algoritma Reserve Unary Codes Untuk Compresi Citra Digital - Gea, Ideli (Jurnal Sains dan Teknologi Informasi, 2024)
Large data sizes result in a waste of storage space required and slow data transfer processes. Compression aims to reduce the size of the data to be as small as possible. Reverse Unary is a type of lossless compression used in this research, which will be measured by Ratio of Compression (RC), Compression and Decompression. The encoding process is only done on image files with jpeg format and encodes using Reserve Unary code, then performs the compression process. From the results of the calculation of the Ration of Compression and Compression Ration of the unary Codes algorithm proves that the reserve unary code is able to reduce data up to 23% in the sense of successful compression, where the data before having a size of 72 MB and after compression the data size is obtained 47 MB.